2017
DOI: 10.1088/1361-6382/aa980b
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of non-manifold-like sets in the causal set path integral

Abstract: While it is possible to build causal sets that approximate spacetime manifolds, most causal sets are not at all manifold-like. We show that a Lorentzian path integral with the Einstein-Hilbert action has a phase in which one large class of non-manifold-like causal sets is strongly suppressed, and suggest a direction for generalization to other classes. While we cannot yet show our argument holds for all non-manifold-like sets, our results make it plausible that the path integral might lead to emergent manifold… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(52 citation statements)
references
References 20 publications
1
43
1
Order By: Relevance
“…This can be viewed as an effective, continuum-like dynamics, arising from the more fundamental dynamics described above. A recent analytic calculation in Loomis and Carlip (2018) showed that a sub-dominant class of non-manifold-like causal sets, the bilayer posets, are suppressed in the path integral when using the BD action, under certain dimension dependent conditions satisfied by the parameter space. This gives hope that an effective dynamics might be able to overcome the entropy of the non-manifold-like causal sets.…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…This can be viewed as an effective, continuum-like dynamics, arising from the more fundamental dynamics described above. A recent analytic calculation in Loomis and Carlip (2018) showed that a sub-dominant class of non-manifold-like causal sets, the bilayer posets, are suppressed in the path integral when using the BD action, under certain dimension dependent conditions satisfied by the parameter space. This gives hope that an effective dynamics might be able to overcome the entropy of the non-manifold-like causal sets.…”
Section: Overviewmentioning
confidence: 99%
“…Indeed, there is a hierarchy of sub-dominant causal sets which are non manifold-like (Dhar 1978(Dhar , 1980Kleitman and Rothschild 1975;Promel et al 2001), with the set of bilayer posets B being the next subdominant class. A recent calculation by Loomis and Carlip (2018) shows that B is suppressed by the BD action when the mesoscale and dimension satisfy certain conditions. The only relations in a bilayer poset are links.…”
Section: A Continuum-inspired Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…One is to construct a quantal version of the classical sequential growth models for causal sets [1][2][3][4] in which causal sets grow in a process of accretion of new elements. In contrast to this process approach, the other strategy is to construct what might be called state sum models where a sum over causal sets -usually of a fixed cardinality -is defined using a weight for each causal set given by the exponential of (i times) an action for the causal set [5][6][7][8].…”
Section: The Causal Set Actionmentioning
confidence: 99%
“…We say that an order C is a convex-rogue if there exists another order D that is not isomorphic to C and that has the same convex-suborders as C. In that case we say that C and D are a convex-rogue pair. 4 Note that the convex-subcausets (convex-suborders) are ordered by inclusion.…”
Section: Convex-subordersmentioning
confidence: 99%